Effect of Different Coffee Brews on Tryptophan Metabolite-Induced Cytotoxicity in HT-29 Human Colon Cancer Cells - Luigi Castaldo; Marianna Toriello; Luana Izzo; Raffaele Sessa; Sonia Lombardi; Silvia Trombetti; Yelko Rodríguez-Carrasco; Alberto Ritieni; Michela Grosso (MDPI AG, 2022)
Coffee consumption positively influences colon health. Conversely, high levels of tryptophan metabolites such as skatole released from intestinal putrefactive fermentation in the presence of excessive dietary animal protein intake, and gut microbiota alterations, may have several adverse effects, including the development of colorectal cancer. Therefore, this study aimed to elucidate the potential protective effects of coffee in the presence of different skatole levels. The results showed that skatole exposure induced reduced cell viability and oxidative stress in the HT-29 human colon cancer cell line. However, co-treatment of cells with skatole and coffee samples was able to reduce ROS production (up to 45% for espresso) compared to cells not treated with coffee. Real-time PCR analysis highlighted that treating HT-29 cells with skatole increased the levels of inflammatory cytokines and chemokines TNF-α, IL-1β, IL-8, and IL12, whereas exposure to coffee extracts in cells that were pretreated with skatole showed anti-inflammatory effects with decreased levels of these cytokines. These findings demonstrate that coffee may counteract the adverse effects of putrefactive compounds by modulating oxidative stress and exerting anti-inflammatory activity in colonocytes, thus suggesting that coffee intake could improve health conditions in the presence of altered intestinal microbiota metabolism.